2019
DOI: 10.1210/jc.2019-01262
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Fasting and Glucose-Stimulated GLP-1 and GIP in Healthy Older Subjects

Abstract: Context It is not known whether glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) levels correlate within individuals, nor whether levels change with age. Previous studies have all been cross-sectional in design. Objective To evaluate longitudinal changes in fasting and glucose-stimulated incretin hormone concentrations in healthy older subjects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…Plasma GLP-1 concentrations were lower at baseline in the older men compared to the younger men but increased more in the older men compared to the younger men after the nutrient drinks, as previously reported [41,42]. A recently published longitudinal study measured GLP-1 concentrations within the same healthy older participants~6 years apart, and found decreased fasting GLP-1 at the follow up compared to the initial study [43]. Similar to CCK, GLP-1 also has satiating effects [39]; however, the sensitivity to GLP-1 in the older population has not been evaluated.…”
Section: Discussionsupporting
confidence: 72%
“…Plasma GLP-1 concentrations were lower at baseline in the older men compared to the younger men but increased more in the older men compared to the younger men after the nutrient drinks, as previously reported [41,42]. A recently published longitudinal study measured GLP-1 concentrations within the same healthy older participants~6 years apart, and found decreased fasting GLP-1 at the follow up compared to the initial study [43]. Similar to CCK, GLP-1 also has satiating effects [39]; however, the sensitivity to GLP-1 in the older population has not been evaluated.…”
Section: Discussionsupporting
confidence: 72%
“…Other longitudinal study showed that a low tertile of GLP-1 response to the oral glucose tolerance test was associated with a steeper increase in fasting glucose level than higher tertiles during 7 years of follow-up [ 23 ]. A recent longitudinal study showed that fasting GIP and GLP-1 and glucose-stimulated GLP-1 decreased significantly over a mean period of 5.9 years and suggested that reduction in incretin hormone responses with aging may predispose one to the glucose intolerance and T2DM [ 24 ]. A major mechanism of action of DPP-4 inhibitors is potentiation of β-cell insulin secretion and inhibition of glucagon secretion by elevating endogenous GLP-1 in a glucosedependent mode of action [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the number is expected to increase to 195.2 million by 2030 and 276.2 million by 2045 [ 42 ]. GLP-1 levels can also be reduced by aging in a fasting and glucose-stimulated state [ 43 ]. However, GLP-1 can reverse the age-associated impairment of insulin sensitivity and glucose tolerance [ 44 , 45 ].…”
Section: The Roles Of Glp-1 Ras In Aging-related Diseasesmentioning
confidence: 99%